Short-term efficacy and toxicity of total neoadjuvant chemotherapy in patients with resectable gastric cancer - A. V. Avgustinovich; S. G. Afanasyev; A. Yu. Dobrodeev; M. Yu. Volkov; D. N. Kostromitsky; L. V. Spirina; O. V. Cheremisina (Сибирский онкологический журнал, 2022)
Background. Currently, perioperative chemotherapy is the standard treatment option for resectable gastric cancer (GC ) at stages higher than T1. Preoperative chemotherapy was shown do not adversely affect the course of the postoperative period in gastric cancer patients. However, approximately 60 % of radically operated patients complete adjuvant chemotherapy. In this regard, the problem arises of postponing all courses of chemotherapy for operable gastric cancer to the preoperative period.The purpose of the study was to analyze short-term efficacy and toxicity of total neoadjuvant chemotherapy with FLOT regimen in patients with resectable gastric cancer.Material and Methods. Since 2020, the Research Cancer Institute of Tomsk National Research Medical Center has been conducting a pilot study, which included 25 patients with resectable gastric cancer (T2–4N0–2M0) who received 8 cycles of neoadjuvant chemotherapy with FLOT regimen followed by radical surgery (gastrectomy or distal subtotal resection of the stomach).Results. Preoperative chemotherapy was completed in 25 (100 %) patients. Side effects that occurred during chemotherapy did not require cancellation or interruption of treatment and reduction in the initial dose of drugs. The most common adverse events were emetogenic reactions (92 %), peripheral neuropathy (60 %), and neutropenia (48 %). All patients had no greater than grade II toxicity, which was reversed with standard maintenance therapy. Radical surgeries were performed 6 weeks after completion of chemotherapy cycle 8. There were no significant postoperative complications (grade III or higher according to the Clavien–Dindo scale) and deaths. The histological examination revealed pathological response of TG R2–3 grade in 21 (84%) patients. Downstaging in both T and N categories was found in 13 (52%) patients.Conclusion. Eight cycles of total neoadjuvant chemotherapy for resectable gastric cancer demonstrates high efficacy, moderate toxicity, and do not adversely affect the course of the perioperative period.